Radix Scutellariae Ameliorates Stress-Induced Depressive-Like Behaviors via Protecting Neurons through the TGFβ3-Smad2/3-Nedd9 Signaling Pathway - Fan Zhao; Chenyiyu Zhang; Dong Xiao; Weihua Zhang; Liping Zhou; Simeng Gu; Rong Qu (Neural Plasticity)
Chronic stress can impair hippocampal neurogenesis, increase neuronal apoptosis, and cause depressive-like behaviors. Our previous studies found that Radix Scutellariae (RS) can rescue the stress-induced neuronal injury, but the mechanism is not clear. Here, we continued to investigate the underlying antidepressant mechanisms of the RS extract. A 7-week chronic unpredictable mild stress (CUMS) procedure was used to establish a murine depression model. 0.75 g/kg or 1.5 g/kg RS was administered daily to the mice during the last 4 weeks. Depressive-like behaviors were evaluated by the sucrose preference test (SPT), forced swimming test (FST), open field test (OFT), and tail suspension test (TST). The neuroprotective effect of RS was evaluated with the expression of hippocampal neuron-related markers and apoptosis-associated proteins by Nissl staining, immunohistochemistry, and western blot. Transforming growth factor-β3 (TGFβ3) pathway-related proteins were detected by western blot. Results showed that RS could ameliorate depressive-like behaviors, increase the expression of the antiapoptotic protein B-cell lymphoma 2 (BCL-2), reduce the expression of the proapoptotic protein BCL-2-associated X (BAX), and increase the number of doublecortin- (DCX-), microtubule-associated protein 2- (MAP2-), and neuronal nucleus- (NeuN-) positive cells in the hippocampus. Moreover, RS could reverse the CUMS-induced decrease of TGFβ3 protein, promote the phosphorylation of SMAD2/3, and increase the expression of downstream NEDD9 protein. These results suggest that RS could exert antidepressant effects via protecting neurons. And the molecular mechanism might be related to the regulation of the TGFβ3-SMAD2/3-NEDD9 pathway.